HUBUNGAN JENIS KELAMIN DAN DOMISILI DENGAN PERTUMBUHAN PADA ANAK DENGAN THALASEMIA - SUSILA ' ILMI; Oswati ' Hasanah; Bay hakki ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2015)
Abstract The aim of this study was to determine the correlation between gender and domicile with growth of children with Thalassemia. This study used correlation method with cross sectional approach. Total sampling method was used to recruit 44 respondents in Thalassemia Center atArifin Achmad General Hospital. The data were analyzed by univariate and bivariate.Chi Square test showed that most of respondents (72.3%) were in school age (6-12 years old), 54.5% are male, 73.7% are primary school students, 54.5% domiciled in Pekanbaru, 52.2% had lenght of thalassemia diagnose 1 until 5 years, and 65.9% in normal growth category. There were no correlation between gender (p value=0.400) and domicile (p value=0.400) with growth of children with Thalassemia. Based on this result, it is recommended for hospital to make some policies related to gender and domicile for children with thalassemia. Keywords : Gender, domicile, growth References : 21 (2004-2014)